DE LO PRIVADO A LO PÚBLICO: LA CELEBRACIÓN DEL ORGULLO LGBTI EN COSTA RICA, 2003-2016 - Jiménez Bolaños, José Daniel (2016)
This article presents an analysis of the LGBTI Pride celebrations (lesbian, gay, transsexual, bisexual and intersex) in Costa Rica between 2003 and 2016, using journalistic documents as primary sources of information. It is argued that these celebrations can be understood as social movements that seek to achieve legal, cultural and in some cases structural equality. The different modalities that these celebrations have had are established, and the paradoxes arising from their dynamics are emphasized. It is argued that in Pride celebration there is a mixture of celebration and political demands, a tension as to the “appropriate” form of representation and the short, medium and long term objectives. As a conclusion, civil rights become the central discursive thrust along all the festivals and marches.